2021
DOI: 10.3390/land10090993
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Evolution and Driving Forces of Sustainable Development of Urban Human Settlements in China for SDGs

Abstract: As the world’s largest developing country, China has actively implemented the UN Sustainable Development Goals (SDGs). Sustainable development of urban human settlements is the result of localization and the deepening of sustainable development theory in China. This study combines SDGs to construct an evaluation index system for the sustainable development of urban human settlements in China, using optimization methods, such as natural breaks (Jenks), exploratory spatial data analysis, and GeoDetector, to cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…For example, in Refs. [39][40][41][42][43][44], SDF is directly used as a common-sense concept without systematic exploration. Specifically, in Ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in Refs. [39][40][41][42][43][44], SDF is directly used as a common-sense concept without systematic exploration. Specifically, in Ref.…”
Section: Discussionmentioning
confidence: 99%
“…Whether in natural or social sciences, it has been found that the terms "impetus", "driving force" and "sustainability" are frequently used. For example, many articles directly use the terms "impetus", "driving force" and "sustainability" in the title [37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…In the early stage of China’s habitat development, the theme of "people-oriented" was neglected [ 68 ], and the existing literature on evaluation is mainly focused on building indicator systems around the habitability, satisfaction, and safety of human settlements [ 5 , 69 ]. In recent years, Chinese scholars have generally considered that human settlements consist of two aspect: soft habitats and hard habitats, and they have also categorized indicators in constructing indicator systems based on the different main functions of urban habitats [ 37 ]. Compared with the existing human settlements indicator system, ours is capable of more specifically and comprehensively assessing.…”
Section: Discussionmentioning
confidence: 99%
“…Krefis et al [ 34 ] pointed out that urban settlements are associated with physical (objective health status), psychological (personal health status) and healthy emotional (emotional well-being) aspects of individuals. Chinese scholars have mainly focused on the research of urban human settlements, including the suitability of human settlements [ 35 ], comprehensive evaluation of human settlements’ quality [ 36 ] and sustainable development of human settlements [ 37 ]. From the perspective of research methodology, with the increasing diversification of research data, research methods have gradually become more abundant, including entropy weight method, analytic hierarchy process, Delphi method, principal component analysis, GIS spatial analysis method [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…As the first battle to achieve high-quality urban development, promoting the sustainable development of the community human settlement system can effectively alleviate the contradiction between people's growing need for a better life and unbalanced and insufficient development [43][44][45]. Currently, scholars at home and abroad focus on the conceptual cognition of human settlement [44,46] and research on human settlement from the perspectives of sustainable development [47][48][49], livability [50,51] and vulnerability [52,53], using a combination of qualitative and quantitative methods such as the questionnaire survey administered to residents [54,55], the entropy method [45,56], GIS spatial analysis [48,57], the coupling coordination degree model [58,59] and the geographical detector model [60]to study the human settlement . The urban human settlement system has been explored and the connotation, components and evolutionary trends of the human settlement system have been clarified.…”
Section: Introductionmentioning
confidence: 99%